Misrepresentation of Islam in the novels of Infidel and Mirage : Ayaan Hirsi Ali and Soheir Khashoggi: religion or culture? - Abdul Jawad, Nouran Farouk (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2009)
This dissertation investigates closely the way Islam has been depicted from the very first days of its advent till our recent days. The historic, religious and economic aspects which played essential roles in creating the image of Islam will be analyzed critically. Various quotes stated by famous historians, politicians, thinkers, writers and poets regarding Islam will be presented and examined. This work will point out the first party who started misrepresenting Islam and will study the reason which led some of the Muslim writers to deform facts about this creed. Accusations that have been circulated against Islam will be resolved. Clarifying the position of women in Islam is the main crux that will be emphasized on in this dissertation. Through criticizing the works of Ayaan Hirsi Ali "infidel" and Soheir Khashoggi "Mirage" the status of Muslim women will be comprehended. A lengthy comparison will be set between the status of women under the law of Islam with females from all different faiths and civilizations. This dissertation will show the reader that justice and respect are the traits which distinguish the treatment of women in Islam from any other. The researcher aims to reveal that both the adherence of manmade customs and cultures contrary to Islam and misapplying Islam are the main reasons behind the injustices placed on Muslim women. It leads to the conclusion that the elevation of the women's position is possible if Islam is adhered to and applied sincerely. This is attainable only when the incorrect culture practices held to by some Muslims are abandoned and ceased. ii